Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/0957650916659578
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of performance of two-stage screw compressor under various operating conditions

Abstract: The screw compressor has a promising application in the process industry due to its appropriate pressure and flow rate. In this paper, a mathematical model of a two-stage oil-free screw compressor is developed to simulate the working process under various operating conditions. The results show that the interstage pressure of the two-stage oil-free screw compressor is built automatically depending on the equal mass flow rate of each stage. It increases with the suction pressure, discharge pressure, and clearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…As shown in Figure 4, the lump model is to describe thermophysical properties of fluids in the control volume in terms of rotating angle by developing differential control equations based on mass and energy conservation. Usually, there are two options of the lump model: m-u model [55][56][57][58][59] and p-T model [17,29,[60][61][62][63]. The former is simpler in equation structures, while the latter consumes less time.…”
Section: Lump Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 4, the lump model is to describe thermophysical properties of fluids in the control volume in terms of rotating angle by developing differential control equations based on mass and energy conservation. Usually, there are two options of the lump model: m-u model [55][56][57][58][59] and p-T model [17,29,[60][61][62][63]. The former is simpler in equation structures, while the latter consumes less time.…”
Section: Lump Modelmentioning
confidence: 99%
“…Leakage is one of the key factors influencing the working process, and mainly affects the volumetric flow rate and volumetric efficiency of screw machines. There are several available leakage models used in the lump model: isentropic nozzle flow [29,55,56,60,61,63,64], orifice flow [17,55,58,61], Lin formula [14,17,55,62,65], uncompressible gap flow [14,65], incompressible and viscous pipe flow [62], adiabatic Fanno flow [59], and one-dimensional steady-state laminar flow [55,57]. Most researchers adopted the same leakage to calculate the flow rate of all leakage paths [17,29,[56][57][58]60,61,63,64], while others adopted different leakage models for different leakage paths considering the different flow states of fluids and the shape of leakage paths [14,55,62,65].…”
Section: Lump Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in power consumption could be achieved by optimizing the intermediate pressure. Liu et al [16] investigated the performance of a two-stage oil-free screw compressor under various operating conditions with a mathematical model. The results showed that the volumetric and indicated efficiency of the second stage is more sensitive to the operating condition than that of the first stage.…”
Section: Introductionmentioning
confidence: 99%
“…A relatively large clearance results in a reduced pump efficiency because there is a significant flow leakage. 13 It is physically difficult to measure the clearance distribution along a contact line between two engaged screw rotors. Therefore, the clearance estimation is a commonly studied issue to enhance the machining accuracy and improve the pump performance.…”
Section: Introductionmentioning
confidence: 99%